2009
DOI: 10.1016/j.ijgo.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Meperidine versus valethamate bromide in shortening the duration of active labor

Abstract: Meperidine, but not valethamate bromide, significantly shortened the duration of active labor in nulliparous women with a singleton pregnancy at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…[13] Also, meperidine was shown to promote cervical effacement during labor[4] and to shorten the duration of active labor in nulliparous women with a singleton pregnancy at term. [5]…”
Section: Introductionmentioning
confidence: 99%
“…[13] Also, meperidine was shown to promote cervical effacement during labor[4] and to shorten the duration of active labor in nulliparous women with a singleton pregnancy at term. [5]…”
Section: Introductionmentioning
confidence: 99%
“…Several trials in the obstetric literature have addressed the efficacy of antispasmodics in reducing the length of the first stage of labor. A Medline search of the English language literature for the period 1937 to February 2011, using as search terms ‘antispasmodics’, ‘spasmolytics’, ‘labor’, ‘augmentation’ and ‘delivery’ alone or in combination, identified 12 comparative trials on the administration of antispasmodics in labor (8–18). We also cross‐checked the references of all selected articles to identify other potentially relevant reports.…”
Section: Discussionmentioning
confidence: 99%
“…Use of anticholinergics/antispasmodics as a method of augmenting labor was first described in 1937 by Hirsch (4), who reported a decrease in labor length by two to four hours following intrapartum administration of an atropine‐like drug (Syntropan®), mainly among older nulliparas. Since then, the popularity of antispasmodics for reducing the duration of labor has varied over time, becoming a routine obstetric intervention in many maternity units throughout the Western world and in parts of the developing world (5–18). Placebo‐controlled randomized trials of different types of antispasmodics used to shorten the length of labor yielded mixed results, with notable success among certain study populations (8–14,16,18) and no appreciable effect in others (7,15,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2–5] But, the effect is not seen consistently and two trials have found no significant effect with the use of this drug. [67]…”
mentioning
confidence: 99%